Tag's ownership transfer protocol based on quadratic residue - Rui XIE; Zhifeng HAO (Dianxin kexue)
A proprietary transfer protocol with higher security and lower cost was proposed.In order to ensure the communication entity authentication premise,two remainder theorems for information transmission encryption were used in the proposed protocol; in the process of mutual recognition of communication entities,the addition of random numbers could make the protocol effectively resist such attacks as replay and desynchronization.After the transfer of ownership occurs,new communication entities would be located.The authentication key needed to be dynamical,so as to reduce the storage space of communication entities.The performance comparison between the proposed protocol and other protocols for safety show that the proposed protocol has the security required for the transfer of ownership and low cost.